Food lipids : chemistry, nutrition, and biotechnology - Akoh, Casimir C., 1955- (CRC Press, Taylor & Francis, 2017)
Maintaining the high standards that made the previous editions such well-respected and widely used references, Food Lipids: Chemistry, Nutrition, and Biotechnology, Fourth Edition provides a new look at lipid oxidation and highlights recent findings and research. Always representative of the current state of lipid science, this edition provides 16 new chapters and 21 updated chapters, written by leading international experts, that reflect the latest advances in technology and studies of food lipids. New chapters: Analysis of Fatty Acid Positional Distribution in Triacylglycerol Physical Characterization of Fats and Oils Processing and Modification Technologies for Edible Oils and Fats Crystallization Behavior of Fats: Effect of Processing Conditions Enzymatic Purification and Enrichment and Purification of Polyunsaturated Fatty Acids and Conjugated Linoleic Acid Isomers Microbial Lipid Production Food Applications of Lipids Encapsulation Technologies for Lipids Rethinking Lipid Oxidation Digestion, Absorption and Metabolism of Lipids Omega-3 Polyunsaturated Fatty Acids and Health Brain Lipids in Health and Disease Biotechnologically Enriched Cereals with PUFAs in Ruminant and Chicken Nutrition Enzyme-Catalyzed Production of Lipid Based Esters for the Food Industry: Emerging Process and Technology Production of Edible Oils Through Metabolic Engineering Genetically Engineered Cereals for Production of Polyunsaturated Fatty Acids The most comprehensive and relevant treatment of food lipids available, this book highlights the role of dietary fats in foods, human health, and disease. Divided into five parts, it begins with the chemistry and properties of food lipids covering nomenclature and classification, extraction and analysis, and chemistry and function. Part II addresses processing and food applications including modification technologies, microbial production of lipids, crystallization behavior, chemical interesterification, purification, and encapsulation technologies. The third part covers oxidation, measurements, and antioxidants. Part IV explores the myriad interactions of lipids in nutrition and health with information on heart disease, obesity, and cancer, with a new chapter dedicated to brain lipids. Part V continues with contributions on biotechnology and biochemistry including a chapter on the metabolic engineering of edible oils.
Keywords: Lipids.; Lipids in human nutrition.; Lipids -- Biotechnology.; Lipids -- Metabolism.; elektronické knihy; electronic books